A New Off-line Measurement Method of Inductance for PMSM - HE Yaping; WEN Yuliang; XU Junfeng; ZHANG Chaoyang; LIU Xiong (Kongzhi Yu Xinxi Jishu)
It proposes a new off-line measurement method of inductance for permanent magnet synchronous motor(PMSM). Voltage, current and rotor position of PMSM are synchronously sampled. Fundamental wave information can be got from DFT (discrete fourier transform) using sampled voltage and current information. Inductance calculation equation can be induced by the voltage steady-state equation. The inductance can be calculated off-line based on Matlab and the torque can be calculated from the measured inductance. This method is verified effective by the comparison between the actual torque and the calculated one.